Large pore mesoporous silicas for application in protein adsorption, enzyme immobilisation and drug delivery - Ritchie, Lyndsey K. (University of St Andrews, 2009)
A range of mesoporous materials based on SBA-15, KIT-6 and FDU-12 have been prepared using neutral block copolymers Pluronic P123 and F127 and characterised using methods including electron microscopy and nitrogen adsorption. Typically the materials have a hexagonal (p6mm) or cubic (Fm3m and Ia-3d) symmetry and pore geometry and are rendered porous by either calcination or solvent extraction. Organic functional groups were incorporated into the silica walls of the materials by co-condensation in the form of propyl thiols and additives in the form of alkanes were added to control pore size and geometry. The effects of temperature, additives, organic functionalisation, synthesis time and sol-gel composition were investigated and the resulting materials were tested as supports for protein adsorption, enzyme immobilisation, and drug delivery. Two FDU-12 materials of differing entrance and cavity sizes were used to adsorb a range of proteins with molecular weight 17 to 160 kDa to determine if there was a size exclusion effect. It was seen that the larger pore material was able to adsorb proteins of a larger size (molecular weight 105 kDa) and an exclusion effect was observed when the dimension of the proteins became too great (larger than 130 kDa). There was no clear trend for the smaller pore material where each protein was adsorbed to some extent by the material but apart from the smallest protein, myoglobin, mainly on the surface and not within the pores. The adsorption of the lipase B from Candida Antartica, CALB, was studied on a range of mesoporous supports with their templates removed by either calcination or extraction. The effect of pore size and functionalisation was investigated in terms of maximum loading and rate of loading. By functionalising the KIT-6 material the maximum loading of CALB was reduced from 45.5 to 32 mg/g whereas functionalising the FDU-12 material increased the maximum from 33 to 42.5 mg/g. The activity of the immobilised CALB was measured by enantioselective transesterification of ...